Outcome of lupus nephritis in childhood onset SLE in North and Central India: single-centre experience over 25 years. (April 2016) - Srivastava, P; Abujam, B; Misra, R; Lawrence, A; Agarwal, V; Aggarwal, A
Introduction: Childhood SLE (cSLE) has a higher prevalence of lupus nephritis (LN), and there are ethnic variations in response to treatment as well as outcome of LN. There are limited data on long-term outcome of LN in cSLE from the Indian subcontinent. Methods: Retrospective analysis of case records of patients with cSLE (satisfying revised American College of Rheumatology (ACR) 1997 criteria for diagnosis) and age of onset <18 years was conducted from 1989 to 2013. Data on clinical features, renal involvement and biopsy findings, treatment, renal outcome, damage accrual and mortality were collected. End-stage renal disease (ESRD) was defined as the need for renal replacement therapy. Actuarial ESRD-free survival was studied as the primary outcome measure using Kaplan-Meier analysis. Results: Among 205 children with cSLE, 134 (121 girls) had evidence of LN. The mean age at disease onset was 13.7 ± 3.5 years and the mean disease duration at presentation was 1.9 ± 2.5 years. Kidney biopsy was available for 92 patients, and histology included: 13 (14.2%) Class II, 24 (26%) Class III, 43 (46.7%) Class IV and 12 (13.1%) Class V LN. The mean follow-up period was 6.75 ± 5.7 years. At last visit, 81 (60.4%) children were in complete remission, 28 (20.9%) were in partial remission, 15 (11.2%) still had active nephritis and 10 (7.4%) had progressed to ESRD. Almost two-thirds (62.9%) of patients experienced lupus flares, and mean flare rate was 0.09 flares/patient follow-up year. Fifty-six (43.8%) children accrued damage and the mean Systemic Lupus International Collaborating Clinics (SLICC)/ACR damage score was 0.79 ± 1.13. Actuarial ESRD-free survival at five, 10 and 15 years was 91.1%, 79% and 76.2%, and five-, 10- and 15-year renal survival was 93.8%, 87.1% and 84%, respectively. Although multiple factors individually predicted poor outcome (death/ESRD), only raised serum creatinine at onset ( R square = 0.65, p  ≤ 0.0001) and damage accrual ( R square = 0.62, p  ≤ 0.0001) remained significant on multivariate analysis. Eleven (8.2%) children died during the follow-up period, and infections were the leading cause of mortality. Conclusions: Long-term outcome of LN in cSLE in our cohort was better than previous reports from India. However, a high rate of major infection still remains the leading cause of mortality.